2018
DOI: 10.1111/exd.13523
|View full text |Cite
|
Sign up to set email alerts
|

SLAM family member 8 is involved in oncogenic KIT‐mediated signalling in human mastocytosis

Abstract: The signalling lymphocytic activation molecule family member 8 (SLAMF8)/CD353 is a member of the CD2 family of proteins. Its ligand has not been identified. SLAMF8 is expressed by macrophages and suppresses cellular functions. No study has yet explored SLAMF8 expression or function in human mastocytosis, which features oncogenic KIT-mediated proliferation of human mast cells. SLAMF8 protein was expressed in human mastocytosis cells, immunohistochemically. SLAMF8 expression was also evident in the human mast ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Studies using mast cell-deficient mice, such as Kit W/Wv mice and Kit Wsh/Wsh mice, revealed that mast cells protect against parasitic infections including Strongyloides ratti and Strongyloides brasiliensis [7,8], as well as the venoms of honeybees or vipers [9]. Mast cells are (KIR) 2DL4 [19][20][21][22][23][24][25][26][27][28][29][30][31]. These include inhibitory receptors characterized by immunoreceptor tyrosine-based inhibitory motifs (ITIMs) within their cytosolic domains ( Figure 1) [32].…”
Section: Introductionmentioning
confidence: 99%
“…Studies using mast cell-deficient mice, such as Kit W/Wv mice and Kit Wsh/Wsh mice, revealed that mast cells protect against parasitic infections including Strongyloides ratti and Strongyloides brasiliensis [7,8], as well as the venoms of honeybees or vipers [9]. Mast cells are (KIR) 2DL4 [19][20][21][22][23][24][25][26][27][28][29][30][31]. These include inhibitory receptors characterized by immunoreceptor tyrosine-based inhibitory motifs (ITIMs) within their cytosolic domains ( Figure 1) [32].…”
Section: Introductionmentioning
confidence: 99%
“…SLAMF8 suppresses the functions of human macrophages 5,6 but has an enhancing effect in human ALK-positive ALCL cell lines and in human KIT-mutated neoplastic mast cell lines 7 . We previously hypothesized that this difference was due to the differential expression of adaptor proteins between human macrophages and KIT-mutated neoplastic mast cells; specifically, human macrophages express the adaptor proteins, SAP and EAT-2, which interacting with SLAMF8 15 .…”
Section: Discussionmentioning
confidence: 98%
“…We previously hypothesized that this difference was due to the differential expression of adaptor proteins between human macrophages and KIT-mutated neoplastic mast cells; specifically, human macrophages express the adaptor proteins, SAP and EAT-2, which interacting with SLAMF8 15 . We are suspecting that these adaptor proteins interfere with the interaction between SHP-2 and SLAMF8 in human macrophage, and the absent expression of SAP and EAT-2 facilitate the interaction between SHP-2 and SLAMF8 in human neoplastic mast cells 7,16 . In this study, we observed SAP-2 and EAT-2 expression in ALK-positive ALCL cell lines (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations